Membandingkan Istilah Arsitektur Tradisional Versus Arsitektur Vernakular: Studi Kasus Bangunan Minangkabau dan Bangunan Bali - Gatot Suharjanto (Bina Nusantara University, 2011)
The term ‘vernacular’ and ‘traditional’ in architecture context actually has a root meaning which is almost the same; both have the same meaning that can be attached to one form of architecture work which is oriented on locality aspects and historiy of its existence. However, how can we distinguish the two terms? One way to find it out is to do a case study on two traditional architecture buildings: Balinese buildings and Minangkabau buildings taken as the sample study. In general, both building have two criteria: culture philosophy and adaptative modernism. Through descriptive analytical methods, the two building types were analyzed to acquire the definition of the building shapes which can be classified whether they belong to vernacular or traditional. The results show that vernacular architecture is a form of original work which is specified with the content and a very strong local and contextual philosophy proper to its time, while the traditional architectural building is a vernacular masterpiece recognized by acclamation and hereditary within a very long time.